Child and adolescent mental health (los Angeles, 2012)
Professionals, academics, and policy makers in the field of child and adolescent development tend to use theoretical frameworks stemming from traditional classified disciplines of psychology, sociology, political science, economics, education, and social work. This book creates an opportunity for experts to use interdisciplinary approaches and perspectives, and provides evidence-based knowledge to deal with the stresses of children and adolescents living in poverty, difficult socioeconomic conditions, and varied cultures. It also conveys the message that shared understandings can promote well-meaning and well-reasoned intervention success in similar contexts across nations in which children and adolescents are growing up in complex and risky environments. The contributors, from multiple disciplines, weave their knowledge around the development of children in contemporary society. They highlight the necessary conversations that schools, families, communities, individuals, and nation-states need to have and, most importantly, the responsibility for everyone to develop an understanding of the mental-health needs of the new generation